Molecular level investigations of coiled-coil proteins - Johnson, Daniel (2006)
The coiled-coil is a very common protein structural motif, consisting of two or more alpha helices intertwined in a supercoil. In biological systems it is found in proteins which fulfil a number of roles, for example in structural proteins such as keratin, as well as a large number of transcription factors and other DNA binding proteins, where it functions as a dimerisation domain. This versatile motif has also been adapted for a number of applications including the production of responsive hydrogels; the construction of self-assembling fibres for tissue engineering applications; as a cross-linking agent in drug delivery applications, as well as in the creation of biosensor surfaces.